Etiology and risk factors of hemorrhagic abomasitis in goat kids - Hossein Esmaeili; Saba Almasi Chegeni; Seyed Mehdi Joghataei; Peyman Lotfalizadeh Mehrabadi; Sara Shokrpoor (Scientific Reports, 2025)
Abstract Hemorrhagic abomasitis, also known as Salivary Abomasum Disease (SAD), is a largely under-researched condition affecting young lambs and kids, often leading to high mortality rates and significant economic losses. The disease’s etiopathogenesis, risk factors, and clinical features remain poorly understood. Existing studies have been limited and fragmented, leading to misdiagnoses and confusion about its true nature. Given the lack of a comprehensive investigation into SAD’s incidence, risk factors, and causative agents, this study aims to provide a thorough analysis through clinical, necropsy, histopathological, microbiological, and molecular examinations. This study involved 633 kids, with 323 in the SAD group and 310 in the control group. A multifaceted approach was utilized, encompassing clinical evaluations, necropsies, histopathological assessments, risk factors, and microbiological and molecular analyses, focusing on investigating virulence genes. During the kidding season, 323 deaths were linked to SAD, with a mean disease duration of 1.34 ± 0.54 days. The highest incidence occurred in the 8–14 day age group, accounting for 51.7% of cases (p < 0.05). The dominant clinical symptoms included weakness, lethargy, depression, failure to suckle, reluctance to move, significantly reduced mobility, unsteady gait, and a withdrawn demeanor. Necropsy findings consistently showed dark hemorrhagic content in the abomasum and characteristic “coffee grain” lesions, with no abnormalities in other organs. Escherichia coli was isolated in 63% of sampled kids, significantly more than in controls (p < 0.03), and confirmed through molecular analysis. Examination of virulence genes highlighted the presence of hlyA, stx1, cnf1, stx2, and eaeA in complex combinations linked to severe abomasum damage. Poor bed and bottle hygiene were identified as the primary risk factors for SAD (p < 0.001), with risk escalating in the later stages of the kidding season as farm conditions deteriorated. This study thoroughly re-evaluates hemorrhagic abomasitis in young kids, delivering valuable and reliable insights into this fatal disease. Based on multifaceted analyses, it strongly indicates E. coli as the primary causative agent.